Adding rebar dia 10mm and 32mm welding works to vol. #20 - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding adding rebar Dia 10mm and 32mm welding works to vol. #20 of BRAC University new campus project.